2000
DOI: 10.1177/00912700022009071
|View full text |Cite
|
Sign up to set email alerts
|

Time to Onset of Analgesia and Analgesic Efficacy of Effervescent Acetaminophen 1000 mg Compared to Tablet Acetaminophen 1000 mg in Postoperative Dental Pain: A Single‐Dose, Double‐Blind, Randomized, Placebo‐Controlled Study

Abstract: This randomized, double-blind, placebo-controlled study compared the time to onset of analgesia and the analgesic efficacy of two formulations of acetaminophen 1000 mg--an effervescent solution and tablet--in 242 patients with moderate or severe pain following dental surgery. Onset of analgesia was determined using a two-stopwatch procedure. Analgesia was assessed over a 4-hour period. Treatments were compared using standard indexes of pain intensity and pain relief and summary measures. Both acetaminophen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 6 publications
0
23
0
5
Order By: Relevance
“…It has been demonstrated that bicarbonate formulations of paracetamol are absorbed faster than ordinary tablets (14,17). The time to analgesic onset has been shown to vary between different formulations with a slower onset for ordinary tablets (18). We could not see any major difference in plasma concentration pattern between the two formulations of oral paracetamol studied, but the low number of patients and sample times should of course be considered.…”
Section: Discussionmentioning
confidence: 74%
“…It has been demonstrated that bicarbonate formulations of paracetamol are absorbed faster than ordinary tablets (14,17). The time to analgesic onset has been shown to vary between different formulations with a slower onset for ordinary tablets (18). We could not see any major difference in plasma concentration pattern between the two formulations of oral paracetamol studied, but the low number of patients and sample times should of course be considered.…”
Section: Discussionmentioning
confidence: 74%
“…No patient required nalbuphine in the ambulatory care unit. There was no difference between groups with respect to the number of rescue analgesic tablets required at home: 6 (2,13), 7 (2,20), and 7 (1,12) for Groups 1, 2, and 3 respectively. The mean times to first request for rescue analgesic medication were similar amongst groups ( Figure 1), as were VAS pain scores measured in the PACU and in the ambulatory care unit (Figure 2).…”
Section: Resultsmentioning
confidence: 92%
“…Postoperative pain after surgical removal of third molar was selected because it is a robust and reliable pain model that has been widely used by investigators, 19,20 and because it is widely performed in our institution on an outpatient basis with adequate pain control.…”
Section: Discussionmentioning
confidence: 99%
“…Many attempts have been made to improve the rate of onset of activity of acetaminophen. For example, soluble tablets have been shown to have a quicker rate of absorption 21 and a faster onset of analgesic action compared with conventional acetaminophen tablets 22 . However, soluble tablets are not always convenient as they have to be dissolved in water prior to administration, and moreover acetaminophen-containing solutions are unpalatable to some patients.…”
Section: Discussionmentioning
confidence: 99%